Integrating Competitive Li+ Coordination with Immobilized Anions in Composite Solid Electrolyte for High‐Performance Li Metal Batteries - Ziyang Liang; Chang Liu; Xiang Bai; Jiahui Zhang; Xinyue Chang; Bo Zhang; Mengxue Xia; Huayun Du; Hao Huang; Bing Wu; Chengkai Yang; Shi Wang; et al. (Advanced Science)
Abstract Poly(vinylidene fluoride) (PVDF)‐based polymer electrolytes have attracted widespread attention due to their unique Li+ transport mechanism. However, their low ionic conductivity and porous structure, as well as residual solvent limit their application at high current densities. Here, a composite solid electrolyte (CSE) is developed by integrating poly(vinylidene‐co‐trifluoroethylene) [P(VDF‐TrFE)] in its all‐trans conformation with aminofunctionalized metal–organic framework (ZIF‐90‐NH2). In such a CSE, all F atoms located on one side of the polymer chain, providing fast Li+ transport channels. Concurrently, the functionalized ZIF‐90‐NH2 can effectively anchor the residual N, N‐dimethylformamide (DMF) in CSEs while weakening Li+‐DMF solvent coordination, inducing the rearrangement of Li+ solvation structure and inhibiting the decomposition of DMF at the interface. Synergistically, ZIF‐90‐NH2 can immobilize anions in Li salts, promoting their dissociation. Based on integrating competitive Li+ coordination with immobilized anions, the obtained CSEs exhibit a high Li+ transference number (0.77). The full cells with LiFePO4 cathode can run stably over 400 cycles at 5 C, while the Li || LiNi0.7Co0.1Mn0.2O2 full cells deliver a high capacity retention (>85%) after 200 cycles at a charge cutoff voltage of 4.5 V. This work opens up a new path for building CSEs with high interfacial stability and fast Li+ transport.